Resource Sharing via Planed Relay for HWN∗. (15th May 2008) - Shen Shen, Chong Chong; Rea Rea, Susan Susan; Pesch Pesch, Dirk Dirk
Abstract : We present an improved version of adaptive distributed cross-layer routing algorithm (ADCR) for hybrid wireless network with dedicated relay stations (HWN ∗ ) in this paper. A mobile terminal (MT) may borrow radio resources that are available thousands mile away via secure multihop RNs, where RNs are placed at pre-engineered locations in the network. In rural places such as mountain areas, an MT may also communicate with the core network, when intermediate MTs act as relay node with mobility. To address cross-layer network layers routing issues, the cascaded ADCR establishes routing paths across MTs, RNs, and cellular base stations (BSs) and provides appropriate quality of service (QoS). We verify the routing performance benefits ofHWN ∗ over other networks by intensive simulation.